Analysis Of Employee Flexitime At The Manta Plus Agency Company - Wijaya, Faiza Rahma (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research aims to analyze the implementation of flexitime policy in Manta Plus agency company. Flexitime, or flexible working hours, has become an increasingly implemented solution in modern companies to help employees achieve work-life balance. Agency companies like Manta Plus, which work in a dynamic environment with tight deadlines, greatly benefit from this flexibility in working time. This research uses a qualitative method with a case study approach. Data collection was done through interviews, observation, and documentation. The purposive sampling technique was used to select informants, namely employees who directly experienced the flexitime policy in the company. The data obtained were analyzed using triangulation techniques to ensure validity and reliability. This research explores how flexitime affects employees' time management, work-life balance, and management of projects that require work schedule adjustments. The flexitime policy allows employees to decide when and where they work, allowing them to work when they are most productive according to their individual needs. This research also examines how this flexibility in working hours impacts teamwork dynamics and the adjustment between varying working times.